The influence of urban spatial configurations on human behaviour and psychological well-being in Malaysia’s urban areas - Mohd Nazry, Muhammad Nazmy Azhary; Ayob, Zulkefle (2025)
The diverse spatial patterns of urban areas in Malaysia shape a complex relationship with residents' behaviour and psychological well-being. This interplay highlights how urban design and spatial configuration interact with human cognition, emotions, and social dynamics. This study explores the relationship between spatial patterns of cities and the behavioural and psychological aspects of people in urban centres of Malaysia. The research examines how urban elements such as structure layout and spatial arrangement, building form and height, and the overall context influence social interactions, stress levels, and mental health. Focusing on the urban context of Pekan Ipoh, data were collected through online surveys administered via Google Forms, targeting a diverse participant group to ensure a representative dataset. The data were analysed using IBM SPSS Statistics 27, employing descriptive statistics and correlation analyses. The results indicate that urban spatial configurations significantly impact behavioural patterns and psychological well-being, emphasizing the importance of well-planned spatial layouts. This study provides valuable insights into the influence of urban design on human experiences. It offers practical recommendations for creating urban environments that promote social cohesion and mental well-being in Malaysia.